Língua Brasileira de Sinais: o domínio dos contrastes mínimos - Lopes, Diéssica Zacarias Vargas (2016)
The present doctoral thesis is an investigation of the perception of minimal contrasts in the Brazilian Sign Language - LIBRAS. To perform this investigation, it was proposed the preparation of an evaluation instrument, to measure how this perception occurs in a modality visual spatial. After the preparation of this instrument, it was applied in two different groups. The first group refers to normal hearing children, with deaf parents, called CODA (Children of Deaf Adults). This group was in LIBRAS development phase. The second investigated group consisted of deaf subjects with LIBRAS acquired. Thus, the total sample consisted of 32 participants, nine in the CODA group aged between two and nine years, which were longitudinally accompanied for one year. In the deaf group, 23 subjects with average age of 14.13 years were evaluated through a cross-sectional study. After data collection, it was performed statistical analysis which considered the variables parameters (hand configuration, location, movement and orientation) and age group for group 1 – CODA. For group 2, which consisted of deaf subjects, was considered as variables: parameters (hand configuration, location movement and orientation), LIBRAS use by the parents, use of LIBRAS out of school, domain of the oral language, domain of the written language, time of diagnosis, beginning of exposure to LIBRAS, time of speech therapy, hearing loss degree, use of hearing aids. The performed statistical analysis considered significance level of 5%, with p<0.05, and the used statistical tests were the comparison tests by Friedman and Wilcoxon; the Spearmen correlation test, as well as the Kruskal-Wallis test to compare the variables among the three groups. The found results from this thesis detected that the parameter movement and hand configuration were those who performed better for the group codas and deaf group respectively, the age group was relevant in the CODA group. In the deaf group, the variable LIBRAS use by parents demonstrated that this criterion was not considered as effective to improve the performance of the subjects in the parameters. In the same group, it was observed that the time of speech therapy was relevant for the perception of the minimal contrasts and the variable beginning of LIBRAS exposure was inversely proportional to the performance of parameters matching. The conclusion is the relevance of studying LIBRAS as a language and also the emphasis of Speech Therapy importance to this area, contributing to the language development of deaf people.